Frequency of neoplasms in canines in Quito, Ecuador - Vinueza, R.L. (2017)
Statistical data of prevalence of neoplasms and risks in canines associated to age, sex and breed are not available in Quito, Ecuador. In the present study, 13 573 medical records from 2011 to 2014 were evaluated to identify animals diagnosed by cytology and histopathology as positive for some type of neoplasm. The prevalence of tumors in the population was 4.94%, and the most frequent location was in soft tissues (39.3%), skin and annexes (24.4%) and in females, in the mammary gland (14.3%). The relative risk of developing tumors was four times higher in animals older than 6 years of age; moreover, the predisposition of males to develop tumours skin and annexes was two times higher than in females. Purebred animals older than four years of age are up to 70% more likely to develop tumors than crossbred dogs of similar age.